2008
DOI: 10.4314/scinat.v4i1.42126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation de l\'activité insecticide de deux plantes <i>Hyptis suaveolens</i> (Linn) et Khaya senegalensis (A. Juss) sur les insectes ravageurs du niébé (<i>Vigna unguiculata</i> L. Walp.)/Use of two insecticidial plants for sustainable cowpea (<i>Vigna unguiculata</i> L. Walp.) protection

Abstract: Evaluation de l'activité insecticide de deux plantes Hyptis suaveolens (Linn) et Khaya senegalensis (A. Juss) sur les insectes ravageurs du niébé (Vigna unguiculata L. Walp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 58%
See 1 more Smart Citation
“…Earlier studies confirmed the insecticidal effects of these plants species: B. ferruginea [45]; B. sapida [15,36,[50][51][52][53]; and K. senegalensis [54][55][56][57][58][59]. Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus.…”
Section: Psychementioning
confidence: 58%
“…Acetone extract of K. senegalensis showed the lowest LC 50 and the biggest toxicity ratio, consequently the most toxic on D. porcellus. Some studies proved efficacy of K. senegalensis for controlling stored products insects such as Trogoderma granarium [59], Callosobruchus maculatus [54,55], and Tribolium confusum [58]. The phytoconstituents found in the leaf extract of K. senegalensis include tannins, saponins, flavonoids, steroids, and alkaloids [37].…”
Section: Psychementioning
confidence: 99%
“…Other studies report quite different composition of the H. spicigera essential oils (Tchoumbougang et al 2005;Sidibe et al 2001). A relatively recent literature reports that essential oils of H. spicigera and H. suaveolens could be a valid option to chemical insecticides for the control of many stored-food pests (Ngamo et al 2007a, b, c;Othira et al 2009;Sanon et al 2006a;Noudjou et al 2007;Kéïta et al 2000;Raja et al 2005;Iloba and Ekrakene 2006;Sanon et al 2006a, b;Kouninki et al 2007;Ngamo et al 2007a, b;Kossou et al 2007), suggesting the necessity of further investigations.…”
Section: Introductionmentioning
confidence: 95%